A Communicative Activities-Based Program to Enhance EFL Secondary Stage Students᾽ Communicative Competence and its Effect on their Success and Failure Attribution - Al Sayed, Mohamed Ezzat Ahmed; Abu Rahmah, Mohamed Ismail; Mohamed, Mohamed Abd El Hamid (جامعة عين شمس - كلية التربية - الجمعية المصرية للقراءة والمعرفة, 2023)
تمثل الدراسة الحالية محاولة لتنمية مهارات الكفاءة التواصلية الرئيسية والفرعية باللغة الإنجليزية كلغة أجنبية لطلاب المرحلة الثانوية من خلال الأنشطة التواصلية، وأثرها على عزو النجاح والفشل لديهم، ولتحقيق هذا الغرض استخدم الباحث نظام المجموعة التجريبية والمجموعة الضابطة، حيث اختار الباحث ستين طالبة عشوائيا من طالبات الصف الأول الثانوي بمدرسة الحسينية الثانوية بنات، إدارة الحسينية التعليمية، محافظة الشرقية، حيث اشتملت المجموعة التجريبية على ثلاثين طالبة، واللاتي درسن باستخدام الأنشطة التواصلية، وثلاثون طالبة للمجموعة الضابطة واللاتي درسن باستخدام الطريقة المعتادة، وقد قام الباحث بإعداد اختبار للكفاءة التواصلية، ومقياس عزو النجاح والفشل وتطبيق كليهما قبليا، وبعديا، وقد استغرقت الدراسة عشر جلسات خلال أربعة أسابيع من الفصل الدراسي الأول للعام الدراسي 2022- 2023 م. وبعد إجراء التحليل الإحصائي توصلت الدراسة إلى أنه للبرنامج تأثير إيجابي في تنمية الكفاءة التواصلية وعزو النجاح والفشل لدى طلاب الصف الأول الثانوي. The current study was mainly intended to develop the EFL secondary schoolers' communicative competence and success and failure attribution through communicative activities. To fulfill this purpose, it adapted the two-group pre-post design, quasi-experimental - control group design. Sixty EFL first secondary schoolers from Hussienia Secondary School for Girls, Hussienia Directorate, Sharkia Governorate, Egypt, were randomly assigned into two groups; thirty schoolers for the experimental group and thirty for the control one. The instruments of the study were a communicative competence test, and success and failure attribution scale. The instruments were pre-post administered to both groups. The current study was conducted over a period of four weeks, over ten session for researching, acting, reflecting and practicing communicative competence, through the first term of the academic year 2022- 2023. Finally, the results of the study revealed that communicative activities-based program had a positive effect on developing the EFL communicative competence and success and failure attribution of secondary stage schoolers.
Keywords: البرامج التعليمية -- التواصل اللغوي -- الأساليب التدريسية -- طلبة المرحلة الثانوية